2008
DOI: 10.1099/vir.0.83358-0
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol transporter ATP-binding cassette A1 (ABCA1) is elevated in prion disease and affects PrPC and PrPSc concentrations in cultured cells

Abstract: Prion diseases are transmissible neurodegenerative disorders of prion protein (PrP) conformation. Prion replication by conversion of benign PrP C isoforms into disease-specific PrP Sc isoforms is intimately involved in prion disease pathogenesis and may be initiated in cholesterol-rich caveolae-like domains (CLD). Concentrations of the cholesterol transporter ATP-binding cassette A1 protein (ABCA1) are elevated in pre-clinical scrapie prion-infected mice and in prion-infected cells in vitro. Elevation of ABCA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Noteworthy, two independent studies revealed that ABCA1 expression is tightly linked with level of PrP res [57,58]. Depletion of ABCA1 by RNA interference decreases PrP res [57] and on the opposite, curing prion infection with pentosan sulfate decreases ABCA1 expression [58], thus suggesting that ABCA1 could be a potential candidate involved in the strong decrease of PrP res we observed in HRS-depleted cells. The mechanism by which ABCA1 could be regulated by HRS is not yet resolved.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Noteworthy, two independent studies revealed that ABCA1 expression is tightly linked with level of PrP res [57,58]. Depletion of ABCA1 by RNA interference decreases PrP res [57] and on the opposite, curing prion infection with pentosan sulfate decreases ABCA1 expression [58], thus suggesting that ABCA1 could be a potential candidate involved in the strong decrease of PrP res we observed in HRS-depleted cells. The mechanism by which ABCA1 could be regulated by HRS is not yet resolved.…”
Section: Discussionmentioning
confidence: 94%
“…Other diseases characterized by cholesterol accumulation in LE/LY with a link to decreased ABCA1 expression and activity are Niemann Pick disease (NPD) type C and B [69,70]. Noteworthy, two independent studies revealed that ABCA1 expression is tightly linked with level of PrP res [57,58]. Depletion of ABCA1 by RNA interference decreases PrP res [57] and on the opposite, curing prion infection with pentosan sulfate decreases ABCA1 expression [58], thus suggesting that ABCA1 could be a potential candidate involved in the strong decrease of PrP res we observed in HRS-depleted cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The representative compound Gly-9 influenced the membrane lipid raft microdomain, suggesting its similarity in action with antiprion compounds such as cholesterol modulators. These compounds are reported to disturb the membrane lipid raft microdomain, a possible site of PrP conversion or interaction between PrPc and PrPsc (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). However, in contrast to these compounds, Gly-9 slightly or never influenced the cell surface PrPc level and the lipid raft-associated PrPc level, but it much more prominently affected the intracellular PrPc level.…”
Section: Discussionmentioning
confidence: 73%
“…Lysates were cleared by centrifuging at 4,400 g for 5 min at 4°C and were stored at 280°C with complete protease inhibitor (Roche Diagnostics Corp.). Samples containing 40 mg of protein were run on 12% SDS-PAGE Tris-glycine gels (Invitrogen, Carlsbad, CA), and Western blotting was carried out as previously reported (26).…”
Section: Protein Analysesmentioning
confidence: 99%